2020
DOI: 10.3389/fnbeh.2019.00276
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State Functional Correlates of Social Cognition in Multiple Sclerosis: An Explorative Study

Abstract: Frontiers in Behavioral Neuroscience | www.frontiersin.org February 2020 | Volume 13 | Article 276 Bisecco et al. RS-FC of Social Cognition in Multiple Sclerosis association between social cognition and RS-FC changes of DMN, EN, and LN in MS. Future studies should further explore the possible adaptive or maladaptive mechanisms of these FC abnormalities in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 73 publications
(84 reference statements)
4
26
0
Order By: Relevance
“…Trim and fill: look for missing studies to left of mean, using random effects model. Imputed mean is random effects.suggested that the domains of cognitive and affective ToM are dissociated, and the function of cognitive empathy/affective ToM in MS is conserved, but cognitive ToM is impaired(74,85,88,93). However, findings from the current quantitative metaanalysis do not support this suggestion, which showed that patients of MS had moderate impairment in both cognitive and affective ToM and their degrees of defect were close (g = −0.72 and g = −0.79, respectively).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Trim and fill: look for missing studies to left of mean, using random effects model. Imputed mean is random effects.suggested that the domains of cognitive and affective ToM are dissociated, and the function of cognitive empathy/affective ToM in MS is conserved, but cognitive ToM is impaired(74,85,88,93). However, findings from the current quantitative metaanalysis do not support this suggestion, which showed that patients of MS had moderate impairment in both cognitive and affective ToM and their degrees of defect were close (g = −0.72 and g = −0.79, respectively).…”
mentioning
confidence: 99%
“…Several studies based on magnetic resonance imaging (MRI) have found that amygdala atrophy is the main predictor of ToM impairment in MS(66,72). Besides, one resting-state functional MRI study found that there was an association between ToM impairment and functional connectivity changes in the default mode network, executive network, and limbic network in MS(74).…”
mentioning
confidence: 99%
“…A few studies used functional MRI (fMRI) to investigate SC in MS (Bisecco et al, 2020; Golde et al., 2020; Jehna et al., 2011; Krause et al., 2009; Labbe et al., 2020; Passamonti et al., 2009). Only one used resting‐state fMRI (rfMRI) combined with RMET (Bisecco et al, 2020) and found no correlation between the functional connectivity (FC) and performances in the test (Bisecco et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies used functional MRI (fMRI) to investigate SC in MS (Bisecco et al, 2020; Golde et al., 2020; Jehna et al., 2011; Krause et al., 2009; Labbe et al., 2020; Passamonti et al., 2009). Only one used resting‐state fMRI (rfMRI) combined with RMET (Bisecco et al, 2020) and found no correlation between the functional connectivity (FC) and performances in the test (Bisecco et al, 2020). However, the performances of patients with MS in the Faux Pas (FP) test, a test of affective and cognitive ToM, were correlated with FC between the right amygdala and the left inferior occipital and visual lateral cortices and with FC between the left cerebellum, the right occipital and visual lateral cortices, and the lingual gyrus (Labbe et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It can assessment the synchronization and the interactions among multiple networks, thus overcomes the shortcomings of timedependent analysis 17 . Its reliability and validity have been verified in the study of a series of cognitive disorders [18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%